How time and perceptions of social context shape employee absenteeism trajectories - Dello Russo, S.; Miraglia, M.; Borgogni, L.; Johns, G. (Journal of Vocational Behavior, 2013)
Although the impact of social influence on employee absenteeism is well established, almost nothing is known about the dynamic, temporal accrual of this influence. Latent growth modeling was used to trace absenteeism trajectories over 4 years for employees who differed in years of organizational tenure. As expected, higher-tenure employees exhibited flat trajectories while those with lower tenure (1–3 years) gradually increased their absenteeism to conform to the dominant norm of the organization. However, as predicted by theories of identification and social exchange, perceptions of social context moderated the latter effect. The more positive an employee's perceptions of top management, the lower his or her rate of increase in absenteeism. The more positive an employee's perceptions of work colleagues, the higher his or her rate of increase in absenteeism. Perceptions of supervisors were unrelated to the rate of change. The study clarifies how employees learn and adapt to organizational absence cultures.